Rayleigh Wave Propagation in an Anisotropic Half-Space with a Graded Piezoelectric Capping Layer and a Non-Ideal Interface - Kholmurodov, Abdulkhamid; Matanov, Muhammad (Engineering, Technology & Applied Science Research, 2026)
This study examines Rayleigh-wave propagation in an anisotropic piezoelectric half-space coated with a functionally graded piezoelectric capping layer, accounting for a non-ideal interfacial condition. The state-space transport equation is first derived from the governing field equations and constitutive relations. The resulting system is then solved to obtain the state-vector transfer matrix and the associated stiffness matrix. An overall surface stiffness matrix is constructed by assembling the contributions of the piezoelectric substrate, the graded capping layer, and the non-ideal interface through appropriate matrix coupling. The frequency–dispersion relation is subsequently formulated by imposing electrically open-circuit and short-circuit conditions, together with a mechanically traction-free boundary condition at the surface. Five graded capping-layer profiles are investigated, in which material properties vary smoothly through the thickness, along with two non-ideal interface models: (i) a dielectric, weakly conducting interface and (ii) a highly conducting yet mechanically compliant interface. Numerical results demonstrate that the Rayleigh-wave phase velocity is strongly influenced by the selected gradient profile, particularly when both mechanical and dielectric interfacial non-idealities are present.